WACANA TUBUH PEREMPUAN DALAM TIGA CERPEN PERIODE TAHUN 2000AN: HA...HA...HA... , MUTILASI, DAN AKAR PULE - Hat Pujiati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2009)
Women bodies as the source of judgments upon women represented by writers from time to time as extension of social discourses or even as counter discourses. Literary works record the movements of the changing discourses of women bodies which have differences in certain period. Beauty, as part of women’s bodies is an endless myth and undeniable by women in the world, is used as a political strategy to get power and to control their bodies. Ideologies embodied in a discourse with their interpellation call and control their subjects for maintaining social relation and domination. Through Foucauldian’s concept of discourse, this text analyzes a discourse of women’s bodies recorded in three Indonesian short stories in certain period: 2000s.